Portfolio optimization on the cryptocurrency market - Bujnošek, Tomáš (2018)
The objective of this bachelor thesis is to make optimized portfolios consisting of only cryptocurrencies, where this particular type of asset was chosen for its rising popularity and author's personal involvement. In the first part, cryptocurrencies are introduced along with their main representative Bitcoin. The following theoretical chapter is focused of portfolio optimization, where the used models Mean-Variance, Mean-CVaR, Mean-Absolute Deviation and Mean-Semivariance are explained. The most extensive and important section of this thesis is the empirical analysis, where 20 cryptocurrencies are analysed and used to create portfolios utilizing the models mentioned above. The comparison of results shows that efficient frontiers are very similar, however models differ in their respective portfolio weights. Any potential investor can then choose a portfolio based on their risk-return preference and put their financial assets into it.